NECESSITY AND IMPORTANCE OF REGIONAL POLICY IN SUSTAINABLE DEVELOPMENT OF REGIONS OF THE COUNTRY - Abdullayev Ilyos Sultanovich; Mullabayev Baxtiyarjon Bulturbayevich (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2023)
This article provides information on the necessity and importance of regional policy in the sustainable development of the country's regions, as well as their theoretical issues are considered and theoretically based scientific recommendations are developed.